Tingkat Pengetahuan Bahaya Pestisida DanKebiasaan Pemakaian Alat Pelindung Diri Dilihat Dari munculnya tanda Gejala Keracunan Pada kelompok Tani Di Karanganyar - Sularti, Sularti (2012)
The Cases of pesticide poisoning in developing countries is very high but high levelsof pesticide useage even in developed countries. Purpose of the study determined the relationship of knowledge and habits of the dangers of pesticides use personal protective equipment (PPE) visible signs of the emergence of symptoms of poisoning in farmers' groups in Karanganyar. This study was a descriptive correlative study with cross sectional design. Purposive sampling of 45 samples obtained sampling. Hypothesis using the chi square test, fisher and logistic regression. The results showed 29 respondents (64%) low knowledge, 16 respondents (36%) were knowledgeable and no higher. PPE usage habits showed 36 respondents (80%) was not complete, 9 respondents (20%) was complete. The emergence of signs of poisoning symptoms showed 30 respondents (67%) appeared, and 15 respondents (33%) did not appear. Hypothesis test results showed no association seen the level of knowledge of the emerging signs of pesticide poisoning symptoms (p = 0.002), there is a usage habits of PPE seen the emergence of signs of poisoning symptoms (p = 0.003) as well as the use of PPE was the custom of the most dominant variable for the appearance of signs of symptoms poisoning (Exp (B) = 0.249).